Microvascular changes in children with MIS-C: a monocentric exploratory study using comparative nailfold capillaroscopy - Taşkın, Sema Nur; Doğantan, Şeyda; Esen, Esra; Sarı, Pınar Garipçin; Çetin, Benhur Şirvan; Paç Kısaarslan, Ayşenur; Poyrazoğlu, Muammer Hakan (Frontiers in Pediatrics, 2025)
BackgroundMultisystem Inflammatory Syndrome in Children (MIS-C) is a severe hyperinflammatory condition that arises after SARS-CoV-2 infection and may lead to endothelial dysfunction and microvascular damage. Despite increasing knowledge on systemic manifestations, microcirculatory involvement in MIS-C remains underexplored.ObjectiveTo evaluate nailfold capillaroscopy (NFC) findings in children diagnosed with MIS-C and compare them with age- and sex-matched healthy controls, thereby assessing subclinical microvascular alterations associated with MIS-C.MethodsIn this cross-sectional study, 25 MIS-C patients meeting CDC criteria and 29 age-/sex-matched controls underwent standardized NFC at 200× magnification by a blinded examiner. Eight fingers (excluding thumbs) were imaged. Morphological parameters (tortuosity, crossing, dilatation, neoangiogenesis, etc.) and quantitative measures (capillary density, lengths, widths, intercapillary distance) were recorded. Tortuosity and crossing were scored semi-quantitatively (0: absent; 1: < 50% affected; 2: > 50% affected). Between-group comparisons used Mann–Whitney U and Chi-square/Fisher tests (α = 0.05).ResultsMIS-C patients had higher rates of tortuosity (92.0% vs. 62.1%, p = 0.010), crossing (64.0% vs. 27.6%, p = 0.007) and dilated capillaries (16.0% vs. 0%, p = 0.040). Apical loop width was reduced (median 12 vs. 14 µm, p < 0.001) and disorganization score increased (p = 0.020). Semi-quantitative scores were higher for tortuosity (p = 0.002), crossing (p = 0.003) and dilatation (p = 0.027) in MIS-C. No meandering, giant capillaries, avascular areas or microhemorrhages were observed.ConclusionNailfold capillaroscopy revealed notable microvascular alterations in children with MIS-C, including increased tortuosity, dilated capillaries, and disorganization. These findings suggest that NFC may serve as a useful non-invasive tool for detecting endothelial dysfunction and early microvascular involvement in MIS-C. Importantly, given the current rarity of MIS-C cases in the post-pandemic era, this study provides a unique and timely contribution, offering one of the few systematic evaluations of microvascular alterations in pediatric MIS-C and establishing a valuable reference point for future comparative research in pediatric vasculopathies.